2018
DOI: 10.4102/sajhrm.v16i0.984
|View full text |Cite
|
Sign up to set email alerts
|

Transformational leadership and employee organisational commitment in a rural-based higher education institution in South Africa

Abstract: Orientation: Transformation is a topical issue in South African higher education institutions. The slow and sluggish progress in attempts to transform the sector can be attributed to leadership and commitment of staff in these institutions.Research purpose: The study investigated perceptions of employees and managers on the connection between transformational leadership style and employee organisational commitment in a selected rural-based higher education institution in South Africa.Motivation for the study: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 19 publications
0
13
0
2
Order By: Relevance
“…Organizational commitment is related to many variables such as intrapreneurial behavior, job satisfaction, relational identification, satisfaction with leadership, readiness for change, commitment to performance, contextual performance, task performance, trust, procedural justice, job engagement, and psychological empowerment. Eleven studies found the effect of transformational leadership on organizational commitment and the variables associated with it (Alamir, Ayoubi, Massoud, & Hallak, 2019;Farrukh, Lee, & Shahzad, 2019;Hijazi & Kasim, 2016;Jyoti & Bhau, 2016;Khattak et al, 2020;Lubega, 2019;Mansur & Guozhu, 2019;Ndlovu, Ngirande, Setati, & Zhuwao, 2018;Pham-Thai, Mcmurray, Muenjohn, & Muchiri, 2018;Xiao et al, 2017;Yeap, Abdullah, & Thien, 2020) . All of these variables can be related to each other because they work at an individual level.…”
Section: Methodsmentioning
confidence: 99%
“…Organizational commitment is related to many variables such as intrapreneurial behavior, job satisfaction, relational identification, satisfaction with leadership, readiness for change, commitment to performance, contextual performance, task performance, trust, procedural justice, job engagement, and psychological empowerment. Eleven studies found the effect of transformational leadership on organizational commitment and the variables associated with it (Alamir, Ayoubi, Massoud, & Hallak, 2019;Farrukh, Lee, & Shahzad, 2019;Hijazi & Kasim, 2016;Jyoti & Bhau, 2016;Khattak et al, 2020;Lubega, 2019;Mansur & Guozhu, 2019;Ndlovu, Ngirande, Setati, & Zhuwao, 2018;Pham-Thai, Mcmurray, Muenjohn, & Muchiri, 2018;Xiao et al, 2017;Yeap, Abdullah, & Thien, 2020) . All of these variables can be related to each other because they work at an individual level.…”
Section: Methodsmentioning
confidence: 99%
“…Those demonstrating TFL can identify the need for change and to gain the agreement and commitment of others in pursuing and driving that change (Louw, Muriithi, & Radloff, 2017). Transformational leaders give a very high priority to their relationships with their followers and demonstrate individualised consideration in meeting their needs for empowerment, achievement, enhanced selfefficacy and personal growth (Ndlovu, Ngirandi, Setati, & Zhuwao, 2018;Odumeru & Ifeanyi, 2013).…”
Section: Transformational Leadershipmentioning
confidence: 99%
“…Overall, transformational leaders are charismatic in behaviour, demonstrate morality in their actions, are congruent and ethical and demonstrate the ability to delegate, to coach and to provide feedback to their teams (Barbuto, 2005;Bass & Avolio, 1994;Odumeru & Ifeanyi, 2013;Xenikou, 2017). Furthermore, they are experienced as being futuristic and inspirational, and they demonstrate the ability to stimulate creativity and innovation (Ndlovu et al, 2018;Yukl, 2002), they create excitement at work through their ability to motivate and inspire others to achieve greater goals and lastly, they demonstrate empathy and nurture one-on-one relationships with subordinates.…”
Section: Transformational Leadershipmentioning
confidence: 99%
“…Transformative leaders have the potentials to suit diverse natural curiosity, interest, and motivation in studies in social-cultural context and school culture (Burgess, 2019;Flaherty & Overton, 2018). The transformative leaders seek the ways to develop teachers' activity and skills to foster student grit for their academic performance, and personal integrity in the cultural context (Ndlovu, Ngirande, Setati, & Zhuwao, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%